Odpowiedzi

Najlepsza Odpowiedź!
2010-02-11T19:13:41+01:00
A)(ulamek)jedna trzecia x-2=x+2
1/3x-2=x+2
1/3x-x=2+2
-2/3x=4 /*3
-2x=12
2x=-12
x=-6
d)(ulamek)x szesc - jedna szosta =1
1/6x-1/6=1 /*6
x-1=1
x=1+1
x=2
e)-2(2x-1)=(ulamek)x trzeciej
-4x+2=1/3x /*3
-12x+6=1
-12x=5
12x=-5
x=-5/12
f)dwie piate (3-x)=-2
2/5(3-x)=-2 /*5
2(3-x)=-10
6-2x=-10
-2x=-10-6
-2x=-16
2x=16
x=8
2010-02-11T19:17:13+01:00
A)
⅓x -2=x+2
-2= 4/3x +2 /-2
-4=4/3x /*3/4
x=-3
d)x/6-⅙=1 /+⅙
x/6=7/6 /*6
x=7
e) -2(2x-1)=x/3 /*3
-12x+6=x /+12x
6=13x /:13
x= 6/13
f)
2/5(3-x)=-2 /*5/2
3-x=-5 /+x
3=x-5 /+5
x=8